2015
DOI: 10.1093/jscr/rjv083
|View full text |Cite
|
Sign up to set email alerts
|

Delayed presentation of a lumbar artery pseudoaneurysm resulting from isolated penetrating trauma

Abstract: Lumbar artery pseudoaneurysms are infrequent complications of penetrating trauma. When present, they are often accompanied by other injuries; however, we report the case of an isolated traumatic lumbar artery aneurysm resulting from a single knife stab. The lesion was successfully treated with endovascular microcoil embolization. While these injuries are uncommon, the surgeon must maintain a high index of suspicion, even with seemingly uncomplicated injuries, as a missed traumatic pseudoaneurysm may be life th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…It was found 2-14 days after the trauma, most frequently on the seventh day [4]. Counihan et al reported delayed bleeding because of a traumatic pseudoaneurysm [5]. In the present case, despite the confirmation of hemostasis by endoscopy, the patient presented with hemothorax one week after the surgery.…”
Section: Discussionmentioning
confidence: 64%
“…It was found 2-14 days after the trauma, most frequently on the seventh day [4]. Counihan et al reported delayed bleeding because of a traumatic pseudoaneurysm [5]. In the present case, despite the confirmation of hemostasis by endoscopy, the patient presented with hemothorax one week after the surgery.…”
Section: Discussionmentioning
confidence: 64%
“…Iatrogenic and posttraumatic causes seem to be the more common types reported in the literature. 5 6 7 8 9 10 11 12 Liu et al recently published a literature review of iatrogenic vascular injuries postspinal surgery. They included 20 case reports totaling 26 patients, of which, 12 patients sustained a pseudoaneurysm during their clinical course.…”
Section: Discussionmentioning
confidence: 99%
“… 12 13 14 15 16 There are several other reports in the literature describing posttraumatic spinal pseudoaneurysms with most patients manifesting their symptoms within 1 year. 5 , 6 , 17 18 19 20 …”
Section: Discussionmentioning
confidence: 99%
“…LA injury is more common in abdominal trauma and knife stab wounds, [1314] but there has been no lack of reports on iatrogenic LA injury, which is more common in spine surgery [69,1518] and urinary surgery. [1920] In a previous meta-analysis, the surgical technical complication incidence associated with PVP (PKP) ranged from 1.8% to 3.8%.…”
Section: Discussionmentioning
confidence: 99%